Mechanical Analysis in Making Teh Tarik - Widiyastuti, Mita; Husein P. Prihanto; Karomatun Nissa; Sherla A. Nisa; Bayu Setiaji (Prodi Fisika Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2022)
Teh Tarik is a tea known as one of the typical Indian drinks. The purpose of this study, to determine the GLB and GLBB resulting from the manufacture of tensile tea, to determine the magnitude of the kinematic and gravitational forces when tea is poured from one glass to another with a fairly high distance. And also to motivate the MSME industry to produce better quality. With the result for GLB: 0.1541; 0.1111022224; 0.1087844444; 0.3073113139; 0.1111022224. And the results obtained for GLBB in a row for tables one to five 4.9142; 5.7649; 5.3892; 6.6331; 3.9648.